[tex]r = \left(\dfrac{33}{13}\right)[/tex]
[tex]s = \left(\dfrac{10}{13}\right)[/tex]
Step-by-step explanation:
Let's multiply and divide the given fraction by the conjugate of the denominator:
[tex]\dfrac{6+\sqrt{27}}{4-\sqrt{3}}×\dfrac{4+\sqrt{3}}{4+\sqrt{3}}[/tex]
[tex]\;\;\;\;= \dfrac{24 + 6\sqrt{3} + 4\sqrt{3} + \sqrt{27}\sqrt{3}}{13}[/tex]
[tex]\;\;\;\;=\frac{1}{13}(24 + 10\sqrt{3} + \sqrt{81})[/tex]
[tex]\;\;\;\;=\frac{1}{13}(33 + 10\sqrt{3})[/tex]
[tex]\;\;\;\;=\left(\dfrac{33}{13}\right) + \left(\dfrac{10}{13}\right)\dfrac{\sqrt{3}}{13}[/tex]
We can see here that
[tex]r = \left(\dfrac{33}{13}\right)[/tex]
[tex]s = \left(\dfrac{10}{13}\right)[/tex]